The association between food preferences, eating behavior, and body weight among female university students in the United Arab Emirates - Haleama Al Sabbah; Abir Ajab; Leila Cheikh Ismail; Leila Cheikh Ismail; Ayesha Al Dhaheri; Sharifa Alblooshi; Siham Atari; Stephanny Vicuna Polo; Malak Amro; Radwan Qasrawi; Radwan Qasrawi (Frontiers Media S.A., 2024)
IntroductionThis cross-sectional study investigated the associations between lifestyle, eating habits, food preferences, consumption patterns, and obesity among female university students in the United Arab Emirates (UAE).MethodsApproximately 4,728 participants, including both Emirati and Non-Emirati students (International Students). Data collection involved face-to-face interviews and anthropometric measurements, showing an interrelated relationship between food preferences and obesity among female university students.ResultsWhile sociodemographic factors and lifestyle habits contribute to obesity, this study uniquely focuses on the role of food preferences and food consumption patterns in body weight status. The findings reveal a significant correlation between the intake of high-sugar beverages-such as milk, juices, soft drinks, and energy drinks-and an increased risk of overweight and obesity among both Emirati and Non-Emirati populations. Notably, milk consumption was particularly associated with obesity in non-Emirati populations (F = 88.1, p < 0.001) and with overweight status in Non-Emiratis (F = 7.73, p < 0.05). The consumption of juices and soft drinks was linked to obesity. Additionally, a significant preference for fruits and vegetables among overweight and obese students was observed, indicating a trend toward healthier food choices. However, there was also a clear preference for high-calorie, low-nutrient foods such as processed meats, sweets, and salty snacks. Fast food items like burgers, fried chicken, fries, pizza, shawarma, chips, and noodles were significantly correlated with increased body weight status, especially shawarma, which showed a notably high correlation with both obesity and overweight statuses (F-values of 38.3 and 91.11, respectively).ConclusionThe study indicated that food choices shape weight-related outcomes is important for designing effective strategies to promote healthier dietary patterns.